‘Wat bedroeft lot is oudt stijf ende arm te wesen’ Waardigheid in verzoekschriften van verarmde Brusselse ouderen, c. 1750-1800. - Verbeke, Anke (TSEG - The Low Countries Journal of Social and Economic History, 2019)
‘How sad a fate to be old, stiff and poor’. Deservingness in almshouse application letters by impoverished Brussels elderly ca. 1750-1800. This article offers a bottom-up perspective to the research on inclusion processes in poor relief in general and elderly care and almshouses in specific at the end of the Ancien Régime. By means of an extensive study of the application letters sent to the Brussels ‘Twaalf Apostelen’ almshouse between 1750 and 1800, the article examines how deservingness is anticipated by the elderly applicants and how it is argued in their discourses. In addition, the article offers insight into the mental framework of these elderly men surrounding coping strategies and channels through which care should or could be obtained. By doing this, the article examines to which extent processes of formalization during previous centuries influenced the mental framework of the elderly during the second half of the eighteenth century.